2012
DOI: 10.1080/09540121.2012.668174
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and change in psychiatric disorders among perinatally HIV-infected and HIV-exposed youth

Abstract: As the pediatric HIV epidemic in resource-rich countries evolves into an adolescent epidemic, there is a substantive need for studies elucidating mental health needs of perinatally HIV-infected (PHIV+) youth as they transition through adolescence. This article examines the role of perinatal HIV infection in influencing mental health by comparing changes in psychiatric disorders and substance use disorders (SUD) in perinatally HIV-infected (PHIV+) and perinatally HIV-exposed, but uninfected (PHIV−) youth over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 33 publications
10
98
2
Order By: Relevance
“…Whether these are higher than in other patient groups with chronic medical conditions, HIV‐exposed but uninfected siblings or well‐matched healthy controls is yet to be fully determined 222, 224, 225, 226. Nevertheless, it is essential that the multidisciplinary team at least monitor for symptoms and signs of psychological distress and mental health disorder, as children progress into adolescence and young adult life.…”
Section: Adolescence Mental Health and Transitionmentioning
confidence: 99%
“…Whether these are higher than in other patient groups with chronic medical conditions, HIV‐exposed but uninfected siblings or well‐matched healthy controls is yet to be fully determined 222, 224, 225, 226. Nevertheless, it is essential that the multidisciplinary team at least monitor for symptoms and signs of psychological distress and mental health disorder, as children progress into adolescence and young adult life.…”
Section: Adolescence Mental Health and Transitionmentioning
confidence: 99%
“…attention deficit hyperactivity disorder), and emotional disorders (e.g. anxiety and depressive disorders) [3][4][5][6][7][8] Psychiatric disorders among children and adolescents with HIV leads to psychological distress and impaired quality of life, increased stigma and isolation and may lead to negative clinical and behavioral outcomes. Despite antiretroviral therapy improving the survival of HIV-infected children, the mental health problems of these children and adolescents have had less attention [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the performance of the PHIV youths was poorer compared to the control group, which consisted of agematched HIV-uninfected volunteers [44] . In regard to mental health, the incidence of psychiatric disorders is higher among PHIV adolescents and uninfected youths belonging to HIV-infected families compared to the general population [45][46][47] . Several studies found that up to 70% of such adolescents meet psychiatric diagnostic criteria.…”
Section: Metabolic Complicationsmentioning
confidence: 99%
“…Several studies found that up to 70% of such adolescents meet psychiatric diagnostic criteria. Some authors found correlations between diagnosis in adolescents and psychiatric disorders among their caretakers [45][46][47] .…”
Section: Metabolic Complicationsmentioning
confidence: 99%